Organizational Socialization and Supervisor Rated Job Performance: The Moderating Role of Value Congruence - Nadeem Ahmed Awan (Corresponding author); Tasneem Fatima (Pakistan Journal of Commerce and Social Sciences, 2018)
The aim of this study is to examine the direct relationship between organizational socialization and supervisor rated job performance along with moderating role of value congruence. The study is time lagged and data is collected in two time lags from the newly joined teachers of different colleges/universities. Sample size of the study is 300. Data was analyzed using Structure Equation Modeling technique and Haye‟s PROCESS model for moderation. The authors found significant direct relationship between organizational socialization and newcomers‟ job performance. Further, moderating role of value congruence in the direct relationship is also proved. The study proves that organizations should hire those employees who have value congruence with organizational values and should focus upon organizational socialization strategies for them to increase their job performance. Moreover, the study proves that value congruence moderates the relationship between organizational socialization strategies and supervisor rated job performance.